Spin–orbit split two-dimensional states of BiTeI/Au(1 1 1) interfaces. (19th March 2019) - Zaitsev, N L; Tonner, R; Nechaev, I A
Abstract: We present an ab initio study of interfaces formed by placing a single trilayer of BiTeI on the Au(1 1 1) surface. We consider two possible interfaces with the parallel and antiparallel orientation of the trilayer dipole moment with respect to the surface normal, i.e. Te–Bi–I/Au(1 1 1) and I–Bi–Te/Au(1 1 1). We show that the resulting interface state that originates from the modified spin–orbit split surface state of the clean Au(1 1 1) surface resides at high energy above the Fermi level and acquires a large spin-splitting and reversal helicity as compared with the original surface state. The former lowest conduction state of the trilayer, which is one of the hitherto known giant Rashba spin-split states of few-atomic-layer structures, becomes partly occupied. In the I–Bi–Te/Au(1 1 1) interface, this state represents a Rashba system with strong spin–orbit interaction, where the outer branch of the spin-split state is mostly populated.